Some Aspects of the Biology and Chemically Assisted Biological Control of Ganoderma Species in Malaysia - Hussin, Mohamad Zakaria (1989)
The biology of Ganoderma parasitic to oil palm and rubber was investigated. The main aspects studied were the morphology of sporophores and basidiospores, and pure culture studies of the isolates with a view to compare their cultural and growth characteristics under different temperatures and hydrogen-ion concen trations of the medium. Ganoderma isolates of oil palm originating from thr ee dif ferent locations namely Kedah, Perak and Selangor in Malaysia exhibited some variations although all belonged to one species, Ganoderma miniatocinctum Stey. Comparisons of oil palm isolates with a confirmed isolate of Ganoderma philippii (Bres. & P. Henn.) Bres. from Hevea rubber revealed that the rubber fungus differed distinctly from oil palm fungal isolates.